Riluzole’s role in treatment of spinal cord injuries – overview of studies on animals and humans - Stołowski, Wenancjusz; Rulewska, Natalia; Grabowski, Filip; Siemko, Jakub; Neska, Dagmara; Prystacka-Szar, Dominika; Stadler-Szajda, Justyna; Czyżnikiewicz, Adrianna; Bujak, Magdalena; Waśniowska, Magdalena (Journal of Education, Health and Sport, 2025)
Injuries in the spinal cord are responsible for disabling a great number of people each year. The primary and secondary damage varies in pathomechanisms, the latter one being heavily associated with excitotoxicity caused by excess extracellular glutamate. Riluzole, a drug used in amyotrophic lateral sclerosis, lowers the amount of released glutamate, thus making it a possible candidate for treatment in spinal cord injuries. Several studies have been performed on animals and humans, although their results do not always align. In controlled environments, when injuries to the neural tissue in the spinal cord are mechanical or ischemic, the drug’s usage shows promising effects in treated rats. Tests on humans are much harder to conduct and so the research has focused on already ill individuals. Their conditions vary, however, and not all of the people could recover, even to a small degree. Further studies need to be performed in order to qualify riluzole as a remedium to injuries of the spinal cord.